THEORY AND PRACTICE OF MANAGEMENT OF FOREIGN EXCHANGE EXPOSURE IN MULTINATIONAL COMPANY (EXPORT/IMPORT ORIENTED COMPANY) - Janda, Tomáš; Brůna, Karel, 1973-; Pour, Jiří; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2015)
Diploma thesis deals with the topic of foreign exchange exposure and approaches to its management. The paper presents in three chapters both the theoretical context of this field, which is during the thesis simultaneously applied on many small examples and eventually on one final case study. The first chapter is dedicated to the theoretical background of the foreign exchange exposure, differentiates its types, methods of quantifications and approaches to its forecasting. The second chapter continues with an explanation of chosen hedging methods, which are further divided into two groups (internal and external). The last chapter presents a case study of a multinational company, where the author analyzed its financial performance, impacts of FX exposure and corresponding methods of management in practice.
Vedoucí práce: Karel Brůna
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses